Development of Traditional Harmony-Based Teaching Materials Based on HOTS to Improve Student Musicality of Music Education Program at Language and Art Faculty at State University of Medan (UNIMED) - Uyuni Widiastuti; Adina S. Sembiring; Muklis Muklis; Hendy Obed Sembiring; Ewin Johan Sembiring (BIRCU, 2019)
The results of this study are: (1) The contents of teaching materials, are at an achievement of 88% with a valid category; (2)Constructor, achieving 84% with a valid category; (3) Language, on the achievement of 82.50 with a valid category (4) Display of teaching materials, on the achievement of 88% with a valid category. The results of the assessment of students consisted of: (1) the display of teachingmaterials was at an achievement of 87.87% with the practical category; (2) user convenience isat 85.52 with a practical category; (3) effectiveness in achieving 67.18 with a very practicalcategory; (4) time effectiveness, in the achievement of 84.69 with the practical category, with anaverage value of achievement of 86.31 with the practical category.